Nurses Knowledge on Management of Patient Receiving Spinal Anaesthesia in a Government Hospital - Rijal, Elisha; Silwal, Suvekshya; Thapa, Sheela; Basnet, Saraswati; Bhagat, Subhadra (Journal of Karnali Academy of Health Sciences, 2019)
Introduction: Spinal Anaesthesia (SA) is a form of regional anaesthesia involving injection of a local anaesthetic into the subarachnoid space. SA is directly related to nervous system, so its mismanagement may cause various complications hence, prevention and management of complication is a vital and complex aspect of critical nursing care. Therefore, the objective of this study was to assess the nurse’s knowledge on the management of patient receiving spinal anaesthesia. Methodology: A cross-sectional descriptive study was conducted among nurses of Koshi Zonal Hospital of Province no. 1, Biratnagar, Nepal from May to June 2017. Non-probability purposive sampling method was used where self-administered questionnaire was administered among 67 working nurses in the hospital. Results: The majority of the respondents (77.6%) belonged to 20-30 years of age group, nearly half (44.8%) of the respondents had completed PCL nursing. Only 67.2% explained the meaning of anaesthesia, and 58.2% had knowledge on physiological changes after SA. Regarding ambulation and cause of backache, 29.9% had knowledge whereas only 20.9% had knowledge about management of post spinal backache. Respondents facing problem to manage the complication after SA was 13.4%. This study also found that the overall knowledge regarding SA was adequate among 80.6% respondents. Conclusion: Nurses as the key personnel in management and prevention of complication, the obtained result was below the desired competence level among working nurses as it is the vital aspect of critical nursing care.